Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1159/000365781
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy and Targeted Therapy in Advanced Biliary Tract Carcinoma: A Pooled Analysis of Clinical Trials

Abstract: Background: In biliary tract cancer, gemcitabine platinum (GP) doublet palliative chemotherapy is the current standard treatment. The aim of this study was to analyze recent trials, even those small and nonrandomized, and identify superior new regimens. Methods: Trials published in English between January 2000 and January 2014 were analyzed, as well as ASCO abstracts from 2010 to 2013. Results: In total, 161 trials comprising 6,337 patients were analyzed. The pooled results of standard therapy GP (no fluoropyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 25 publications
(31 reference statements)
1
26
0
2
Order By: Relevance
“…Advanced or unresectable locally advanced disease has a poor prognosis with limited systemic treatment options. 1 Combination platinum-gemcitabine chemotherapy is an active first-line treatment regimen; 2 however, it is associated with low rates of radiologic response and short time to tumour progression. Effective new treatments are therefore urgently required.…”
Section: Introductionmentioning
confidence: 99%
“…Advanced or unresectable locally advanced disease has a poor prognosis with limited systemic treatment options. 1 Combination platinum-gemcitabine chemotherapy is an active first-line treatment regimen; 2 however, it is associated with low rates of radiologic response and short time to tumour progression. Effective new treatments are therefore urgently required.…”
Section: Introductionmentioning
confidence: 99%
“…In 2007, a pooled analysis of 104 clinical trials, including 2810 treated patients, showed better response rate (RR, 28% vs 15.3%, P = 0.000), disease control rate (DCR, 61% vs 50.4%, P = 0.000), time to progression (4.4 vs 3.4 months, P = 0.015) and a trend for improved OS (median 9.3 vs 7.5 months, P = 0.061) for doublet chemotherapy compared with monotherapy. 19 Interestingly, the same study suggested gemcitabine combined with cisplatin or oxaliplatin as the most active regimen based on increased RR and DCR as compared with other combinations.…”
Section: First-line Chemotherapymentioning
confidence: 99%
“…Addition of fluoropyrimidine or gemcitabine based chemotherapy plus targeted therapy mainly against epidermal growth factor receptor yielded even better outcomes compared to gemcitabine platinum alone. 132 …”
Section: Chemotherapy For Unresectable or Metastatic Diseasementioning
confidence: 99%